PSMA PET/CT scan reveals incidental meningioma in a prostate cancer patient - Venetia A. Florou; Aditya Halthore; Calixto-Hope G. Lucas; Carlos A. Rivera Lopez; Kenneth J. Pienta (Urology Case Reports)
As PSMA-PET/CT is routinely used for prostate cancer diagnosis due to its improved accuracy over traditional imaging techniques, an increasing number of non-prostate lesions are also being identified. Here, we report a patient with prostate adenocarcinoma, who was diagnosed with a synchronous atypical meningioma during PSMA PET/CT staging. Although PSMA PET/CT is a valuable tool in prostate cancer management, its limitations must be considered when assessing non-prostate lesions to minimize the risk of diagnostic errors.